Significantly Improved Energy Storage Density of Polypropylene Nanocomposites via Macroscopic and Mesoscopic Structure Designs - Ji, Minzun; Min, Daomin; Wu, Qingzhou; Mi, Rui; Liu, Wenfeng; Li, Shengtao; Qin, Shaorui; Zhu, Shenglong (Frontiers in Electronic Materials, 2022)
Polymer dielectrics with high breakdown strength are very competitively used in the dielectric capacitor which is widely applied in pulsed power devices and power systems due to its ultra-high-power density. Polypropylene (PP) film is the most popular used polymer for the dielectric capacitor in the market. However, its low energy density can’t meet the emerging demand of miniaturized, compact, and high-energy performance dielectrics. Therefore, it is urgent to raise the energy storage density of polypropylene film. Here, this paper described the improved energy storage density of polypropylene nanocomposites via macroscopic and mesoscopic structure design. The ABA-structured, BAB-structured, and single-layered nanocomposites were prepared by melting blending and hot-pressing methods, where “A” and “B” films refer to PP/MgO and the PP/BaTO3 nanocomposite dielectrics, respectively. Then the microstructure, dielectric, breakdown and energy storage properties of these nanocomposite dielectrics were tested. According to the test results, for the sandwich-structured dielectrics, the B layer and the interface between adjacent layers can increase the polarization, the A layer and the barrier at the interface can reduce the charge mobility. In addition, the sandwich structures can redistribute the electric field. Correspondingly, the breakdown strength and permittivity of PP dielectrics are improved synergistically. Compared with the PP nanocomposite dielectrics with BAB structure, the one with ABA structure exhibits more excellent energy storage performance. The largest energy storage density of ABA films with a BaTO3 content of 45 wt% in the B layer is 3.10 Jcm3, which is 67% higher than that of pure PP. The study provides a new concept for improving the energy storage performance of polymer nanocomposite dielectrics from the perspective of macroscopic and mesoscopic structure design.